Non-linear characteristics of the sterling/european currency unit exchange rate: 1984–1992 - Chappell, D.; Eldridge, R.M. (International Journal of Phytoremediation, 1997)
The behaviour of the Sterling/European Currency Unit (ECU) exchange rate is examined both during the time before Britain joined the European exchange rate mechanism (ERM) and during the time of Britain's membership. During the latter period, a GARCH (1, 1) model fits the data well but during the pre-ERM period there is evidence of significant non-linear - possibly chaotic - structure in the GARCH residuals. Analysis of the dominant Lyapunov exponents and correlation dimension for the pre-ERM period suggests that the data generation process may be chaotic and this is reinforced by the highly significant BDS statistics obtained for this sample period. © 1997, Taylor & Francis Group, LLC.
1 citations (Crossref) [2023-10-31]
Keywords: Non-linearity; Sterlingecu exchange rate; dept.eco; dept.fin

The effect of zoning on housing construction - Thorson, James A (Journal of Housing Economics, 1997)
This paper examines whether a more restrictive zoning ordinance actually reduces construction of new housing. This may seem at first to be a trivial issue, since why else would a zoning board make the ordinance more restrictive. However, it is possible for landowners to circumvent the zoning law. For example, they can subdivide their land before the zoning change occurs. In addition, they can bargain with the local zoning officials and offer side payments, also known as exactions, for the right to develop their land. This paper examines a famous case of agricultural downzoning in McHenry County, Illinois. It finds that although the number of building permits issued did not fall immediately, in the long run the number of permits issued by the county was significantly reduced. This suggests that developers were able to anticipate the zoning change and subdivide their land before it occurred. (C) 1997 Academic Press.
31 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/024-739-138-771-737 tex.type: [object Object]
Keywords: dept.eco; dept.fin